KARAKTERISASI NILAI IC50 DAN KADAR KURKUMIN PADA TABLET EFFERCVESCENT EKSTRAK KUNYIT YANG DIPERKAYA VITAMIN C - Arief Rakhman Affandi; Ary Susatyo Nugroho; Umar Hafidz Asyari Hasbullah (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
During the pandemic, nutraceuticals are needed to boost immunity. Indonesia is one of the countries that has the potential to produce nutraceutical goods based on rhizomes like ginger, turmeric, temulawak, and other types of rhizomes. These rhizomes have been used for medicinal purposes for thousands of years. This refresher contains significant health-promoting effects. Turmeric contains several components of active compounds that can act as antioxidant compounds and increase body immunity. Effervescent tablets are one sort of food product that could be made utilizing turmeric as an ingredient. The purpose of this study was to develop a formula for effervescent tablets that make use of turmeric extract and are mixed with vitamin C, which is known also to aid increase body immunity and other bodily health functions. The design is a Complete Randomized Design (RAL) Factorial pattern employing two factors: turmeric extract (30 40 %b/b) and vitamin C (5, 10, 15 %b/b). The experimental responses that were used were the solubility time, the pH value of the solution, and the antioxidant capacity (IC50 value). An increase in vitamin C concentration is associated with a corresponding rise in solution pH, which, according to SPSS analysis, reaches a maximum value of 3.96. Effervescent tablets with 40% turmeric extract and 15% vitamin C have the lowest IC50 value (0.89 mg/ml). The result represents the product's antioxidant potential to ward off free radicals in a reasonable level. This formula also has the quickest solubility time when compared to other formulae for the fabrication of effervescent tablets, with a time range of 190 seconds for 1 tablet (± 3 grams).